“Evaluación de las características morfológicas y agronómicas del cultivo de maíz (Zea Mays l.) Sometido a tres densidades de siembra en la zona de ventanas, provincia de los Ríos.” - Villacís Seme, Jennifer Yamali (2021)
The research work was carried out in the vicinity of the "La Victoria" farm, located at km 32 on the road to Ventanas canton, province of Los Ríos, and consisted of evaluating experimental lots of corn, using a simple hybrid (Centella) at different planting distances. Three treatments were evaluated: T1 (60 x 20 cm), T2 (70 x 20 cm) and T3 (80 x 20 cm), arranged in an ACD with five replications. The variables evaluated were: plant height (cm), stem diameter (cm), ear row number, ear length (cm), ear diameter (cm), 100-seed weight (g), grain yield (kg/ha), phenology and economic analysis. In terms of plant height, stem diameter and number of ear rows, there were no significant differences between treatments, while in the variables ear length and diameter, 100-seed weight, grain yield and net income of the economic analysis, T1 stood out over the other treatments. However, in this last variable, it is important to note that T2 showed a better benefit/cost ratio, registering higher earnings per dollar of investment. Finally, in terms of phenology, six of the most relevant stages were identified, namely: VE, V2, Vn, Vt, R1 and R4. Keywords: Corn, simple hybrid, density, yield.